Kreativitas Motif Batik Sebagai Penguat Budaya Bangsa di Dharma Wanita LLDIKTI VII Jawa Timur - Herlina, Yekti; Sufiana; setiawan, andri (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2025)
Dharma Wanita is a national professional organization that has a vision and mission to improve the ability of civil servants' wives and civil servants themselves who are women in the future so that they can become intelligent women, have knowledge, become pious wives to become pillars in the family, to support fathers or husbands. That behind the success of a man there must be a great woman. Dharma Wanita Persatuan (DWP) LLDIKTI Region VII consists of wives of employees in the LLDIKTI VII environment, Women's Association, Academic Community of Higher Education in the LLDIKTI VII Environment. Activities held such as seminars, to support family welfare and national progress Holding social activities, Batik skills, Cooking, Facial Acupressure Beauty, This activity method is focused on members of DWP LLDIKTI VII who collaborate with STKW Surabaya to introduce batik creativity in developing and increasing batik skills as a strengthener of national culture and building independent Indonesian women. Batik as a noble work of art of the Indonesian nation has a distinctive and unique beauty that distinguishes it from other textile decoration patterns. The uniqueness of the appearance of batik is produced from specific materials, tools, and processes that require perseverance, craftsmanship, patience and high creativity. The results of this service support one of the Dharma Wanita Persatuan LLDIKTI VII programs, namely training to improve batik skills as a strengthener of national culture for independent women. It is hoped that various kinds of knowledge about batik from making batik patterns, transferring batik patterns to cloth, attaching wax to cloth using canting, dipping cloth into dye and drooping. It is hoped that it can add inspiration and innovation for the development of Independent Indonesian Women in the future.